Climate Security in the MENA Region - Läderach, Peter R.D.; Merrey, Douglas J.; Schapendonk, Frans; Dhehibi, Boubaker; Ruckstuhl, Sandra; Mapedza, Everisto D.; Najjar, Dina; Dessalegn, Bezaiet; Amarnath, Giriraj; Vinay, Nangia; Al-Zu’bi, Maha; Biradar, Chandrashekhar M.; et al. (2022)
The evidence on conflicts around the world since the turn of the century points to a simple conclusion: conflicts, grievances and insecurities are increasingly being affected by changing climates, environmental degradation, food insecurity, and the struggle to control a finite pool of natural resources. This paper aims to understand the linkages between climate, conflict, agriculture, and migration in the Middle East and Northern Africa (MENA) region and offer a road map for the region while emphasizing the role of research and development. We do this by first clarifying what climate security means and how it links to risk and resilience (Introduction). We then present causal impact pathways to describe how climate exacerbates drivers of conflict and insecurity (Section 2). This is followed by an overview of indicators summarizing the state of climate security in MENA and a discussion of the limitations of such indicators (Section 3). We also identify climate security and climate peace hotspots in the region using spatial analysis (Section 4). We then present existing research for development efforts and discuss their potential to contribute to climate security by mitigating its drivers with a specific focus on gender inequality (Section 5). We offer entry points for improving climate security using sustainable finance (Section 6). This is followed by a series of case studies (Section 7 to 11) and finally Section 12 concludes by emphasizing the key findings of the paper.